Active solar systems - Löf, George O. G. (Solar heat technologies, 1993)
Active Solar Systems is volume 6 in a series that surveys advances in solar energy research since the oil shock of the early 1970s. Books in the series document in particular the period 1973 to 1985, which spawned a rich array of federally financed technological programs and developments facilitating the practical use of solar energy.The twenty-two contributions in Active Solar Systems introduce design, analysis, and control methods for active systems and cover advances in the interconnected technologies for water heating, space heating, and space cooling. They show that, with effective marketing and with environmental costs factored into individual consumer decisions, there is strong potential for solar water heating and space heating, and that solar cooling has potential but needs further development to become commercially viable. The details of the materials involved in these technologies are covered in volume 5, Solar Collectors, Energy Storage, and Materials.George Löf{ is Professor Emeritus and Senior Advisor in the Solar Energy Applications Laboratory at Colorado State University.